GEOPOLITICAL CONFLICTS IN THE RED SEA AND THEIR POLITICAL AND ECONOMIC IMPACTS ON YEMEN - Sanaa Hikmat Hasan Mahmood (Universitas Negeri Malang, 2026)
The Red Sea is a strategic international waterway linking Asia, Africa, and Europe, playing a crucial role in global trade, energy security, and maritime stability. At its southern entrance lies the Bab al-Mandab Strait, a narrow yet vital shipping route through which a significant portion of global oil and commercial traffic passes. Yemen’s geographic position along this strait makes it a pivotal but highly vulnerable actor in regional geopolitics. Since the escalation of the Gaza conflict, tensions in the Red Sea have intensified as Yemeni forces targeted vessels associated with Israel and Western countries, increasing maritime insecurity and geopolitical confrontation. In response, the United States, the United Kingdom, and allied states conducted multinational naval operations aimed at ensuring freedom of navigation, although these actions were widely viewed as demonstrations of strategic power in a critical maritime corridor. The conflict has generated substantial economic consequences, including disruptions to international shipping routes, rising insurance and freight costs, supply chain instability, and inflationary pressures on global energy and food prices. Many shipping companies redirected vessels through the Cape of Good Hope, increasing transportation time and operational expenses. For Yemen, already affected by prolonged civil war, economic collapse, and humanitarian crises, these developments worsened conditions through currency depreciation, reduced trade activity, and growing food insecurity. This study examines geopolitical conflicts in the Red Sea from 2019 to 2025 and analyses their political and economic impacts on Yemen, focusing on maritime insecurity, regional power competition, and the broader implications for global economic stability.